2020
DOI: 10.1589/jpts.32.140
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between radiographic sagittal alignment, range of motion, muscle strength, and quality of life in adults with spinal deformities

Abstract: The aims of this study were to examine the relationship between range of motion/muscle strength of the spine and lower limbs with 1) radiographic sagittal alignment and 2) quality of life of participants with spinal deformities to adequately target the appropriate factors for effective treatment. [Participants and Methods] This study used an observational cross-sectional correlational design. Participants with spinal deformities and low back pain were recruited for the study. The dependent variables were range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…The correlation between FHP and cervical disability, postulated in numerous studies [7,[10][11][12][13][14][24][25][26][27], is not confirmed in our series. The cervical pain symptom and the relative cervical disability, confirmed by a score on the NDI questionnaire > 8, are not strictly correlated to the presence of FHP; among the 45 subjects who presented with FHP, only 11 of these reported suffering frequently from neck pain (NDI > 8), while the remaining 34 subjects with FHP were asymptomatic.…”
Section: Discussioncontrasting
confidence: 87%
“…The correlation between FHP and cervical disability, postulated in numerous studies [7,[10][11][12][13][14][24][25][26][27], is not confirmed in our series. The cervical pain symptom and the relative cervical disability, confirmed by a score on the NDI questionnaire > 8, are not strictly correlated to the presence of FHP; among the 45 subjects who presented with FHP, only 11 of these reported suffering frequently from neck pain (NDI > 8), while the remaining 34 subjects with FHP were asymptomatic.…”
Section: Discussioncontrasting
confidence: 87%
“…Typical symptoms characteristic of LSS might be neurogenic intermittent claudication, lower extremity pain, and numbness and weakness in the lower extremities [ 11 ]. In contrast, back pain and standing gait disturbance due to forward-stooped posture is one of the representative symptoms of ASD [ 12 ]. Additionally, adult spinal deformity has been reported to be correlated with many symptoms not only of musculoskeletal disorders but also possibly of disorders of visceral organs close to the spine such as gastroesophageal reflux disease and pulmonary dysfunction [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous development of medical technology, many spinal diseases can be treated by surgery, and the complications brought by spinal surgery have been paid more and more attention. Spine surgery incision infection (SSI) is one of the common complications of spinal surgery, with an incidence rate of 0.7%-12% reported in the literature [1,2]. SSI not only affects the patient's surgical results, but also causes medical burden of patients.…”
Section: Introductionmentioning
confidence: 99%